PHENOLIC TOTAL CONTENT AND ANTIOXIDANT ACTIVITY OF ETHANOL EXTRACT OF MARKISA KONYAL (Passiflora ligularis) SEEDS - Sari, Tisa Mandala; Verawati; Revi Yenti; Ayu Anggraini (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Konyal passion fruit (Passiflora ligularis f. lobata) has been widely used as fruit juice by the community, it is necessary to conduct research to explore the potential of konyal passion fruit as a natural medicine. This study aims to determine the total phenolic compound content and antioxidant activity of ethanol extract from konyal passion fruit seeds using UV-Vis Spectrophotometry method. The sample was macerated with 70% and 96% ethanol solvent, repeated three times and the filtrate was concentrated using a rotary evaporator at 40°C. The extract obtained was determined by the concentration of phenolic compounds using the Follin - Ciocalteau method and the antioxidant activity test using the DPPH method with gallic acid as a comparison compound. The determination of the total phenolic compound content was obtained at 77,73 µg/mL at a wavelength of 747 nm. The antioxidant activity test of gallic acid obtained IC50: 2,04 µg/mL, and the antioxidant activity test of the sample obtained IC50: 21,89 µg/mL at a wavelength of 515 nm. Based on the IC50 value, it can be concluded that the antioxidant activity of the ethanolic extract of passion fruit seeds is in the very strong category, namely in the range <50 µg/mL. The equivalence of antioxidant activity of ethanolic extract of konyal passion fruit seeds with gallic acid is 1:10,73 mg, meaning that 1 mg gram of gallic acid is equivalent to 10,73 mg of ethanolic extract of konyal passion fruit seeds.